Bidirectional Gender Face Aftereffects: Evidence Against Normative Facial Coding. (February 2017) - Cronin, Sophie L.; Spence, Morgan L.; Miller, Paul A.; Arnold, Derek H.
Facial appearance can be altered, not just by restyling but also by sensory processes. Exposure to a female face can, for instance, make subsequent faces look more masculine than they would otherwise. Two explanations exist. According to one, exposure to a female face renormalizes face perception, making that female and all other faces look more masculine as a consequence—a unidirectional effect. According to that explanation, exposure to a male face would have the opposite unidirectional effect. Another suggestion is that face gender is subject to contrastive aftereffects. These should make some faces look more masculine than the adaptor and other faces more feminine—a bidirectional effect. Here, we show that face gender aftereffects are bidirectional, as predicted by the latter hypothesis. Images of real faces rated as more and less masculine than adaptors at baseline tended to look even more and less masculine than adaptors post adaptation. This suggests that, rather than mental representations of all faces being recalibrated to better reflect the prevailing statistics of the environment, mental operations exaggerate differences between successive faces, and this can impact facial gender perception.